Preputial Reconstructive Surgery to Correct Traumatic Balanoposthitis Induced Paraphimosis in A Bull - Ahuja, A.; Kumar, A.; Sachin; Chauhan, M.; Sood, P.; Sharma, A. (The Indian Journal of Animal Reproduction, 2021)
A non-descript bull was presented with paraphimosis. Penile examination  revealed severely edematous preputial sheath leading to preputial prolapse  and a severely inflamed penis having single traumatic region in the middle  of the shaft. After providing necessary medication, the bull was restrained  and laid down in left lateral recumbency. The local infiltration of lignocaine  hydrochloride and adrenaline was done around the proximal preputial  sheath along with the orifice. A 1.2 cm long equilateral triangular portion  (contralateral to the side of recumbency) on the free area of prepuce was  carefully dissected, preventing the injury to peri-penile elastic layers. The  apex of the dissected triangular portion pointed towards the root of the  penis. Similar procedure was repeated on the other preputial side (left  lateral) by laying the bull in right lateral recumbency. The sutures were  removed two weeks after the surgery and bull recovered uneventfully.
Keywords: Balanoposthitis; Paraphimosis; Preputial reconstruction; Bull; Preputial prolapse